Islamic Ethics of Disability: A Sunnah-Based Model for Social Integration - Ayu Ariska; Tarmizi Tarmizi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This research aims to investigate the foundational principles governing Prophet Muhammad’s interactions with people with disabilities, ultimately formulating a normative model for Islamic-based social integration. The study addresses the unfortunate reality that people with disabilities continue to face persistent marginalization and stigma within contemporary Muslim societies, despite the strong ethical teachings of Islam. This paper offers a crucial new perspective by shifting the focus of Islamic disability studies from traditional theological and juridical approaches toward a sociological analysis rooted in the Prophet’s actual social practices.The methodology employed is qualitative library research, utilizing primary data from the Hadith, Sīrah (Prophetic biography), and classical Islamic texts, complemented by secondary data from contemporary scholarly literature. The analysis is conducted using a descriptive-analytical approach, synergistically applying Émile Durkheim’s theory of social solidarity, Pierre Bourdieu’s concepts of habitus and social capital, and John Rawls’ theory of justice.The findings demonstrate that the Prophet’s interactions were not merely acts of moral compassion but rather reflected a systematic effort to build social participation and responsibility among people with disabilities. This was achieved through the deliberate provision of symbolic capital (honor and recognition), the elimination of stigma, and the active provision of equal social access. The novelty of this research is the formulation of a Sunnah-based social inclusion model that integrates Islamic values with modern sociological theory, thereby explicitly enriching the discourse on modern social integration and global disability studies, while also serving as an inspiration for policies and empowerment strategies for persons with disabilities in contemporary society.